Spinoza en Deleuze: cartas políticas - Lafferranderie, Emilio J. (2015)
To think a Deleuzian politics requires to understand the philosophical markleft in his work by Spinoza. Both philosophers’ paths crisscross in their problems, questions and consequences. In this paper three concepts will be put in relation: critique, right and crowd. The aim is to elucidate how man can open new ways of political experience from the conjunction of two philosophies articulated upon a common ground: immanence and life.